Local anesthesia for Reduction of Nasal Bone Fracture: our experience - Qais Aljfout; Ahmed AL-Btoush; Abdelrazzaq Alrefo; Nidal Al-Soud; Tamara a.Obeidat (International Journal of Medical Research and Review, 2017)
Introduction: Nasal bone fractures are very common injuries, reduction under local anesthesia is the usual management, yet there is controversy about the efficacy of this management and if it satisfies the patient's functional and cosmetic needs.Objective: To assess both efficacy of nasal bone reduction under local anesthesia and patient's degree of satisfaction in regards to aesthetic and functional results.Patients and Methods: Retrospective analysis and review of 31 patients underwent nasal bone reduction under local anesthesia in Prince Hashim Military hospital in Zarqa, Jordan between May 2015 and June 2016. Digital and instrumental reduction under local anesthesia was performed with and without splint application after clinical and radiological assessment. Results were evaluated by objective clinical examination and subjective functional and cosmetic satisfaction.Results: Patients were divided into two groups according to gender, group A: males 23 (74.19%), group B: females 8 (25.8%), 20 patients of group A (86.95%) were happy with the functional and cosmetic outcome, 3 patients of group A (13.04%) were not happy with the cosmetic outcome but happy regarding the functional outcome, 5 patients of group B were happy with the functional and cosmetic outcome, 3 patients of group B were not happy regarding the cosmetic outcome but satisfied with the functional outcome, all patients in both groups except one patient in group A were had patent nasal airway on clinical and endoscopic examination. 2 patients from both groups sought revision surgery for cosmetic concerns only.Conclusion: Use of local anesthesia for reduction of nasal bone fractures offers both patent nasal airway and satisfactory cosmetic results.